Gambaran persalinan prematur pada kehamilan remaja di RSUP Prof. Dr. R. D. Kandou Manado periode 1 Januari – 31 Desember 2015 - Ondang, Marnie Ch.; Suparman, Eddy; Tendean, Hermie M.M. (Universitas Sam Ratulangi, 2016)
Abstract: According to WHO, about 13 millions babies were born prematurely in this world, and less than 1 million premature babies die every year. Around 14 million teenagers become mothers every year and more than 90% of young mothers were in developing countries. Rate of premature birth around 10-20% in Indonesia in 2009 which causes Indonesia becomes the big 5 of the most premature births. According to Riskesdas in 2013 pregnancy in the age 10-54 years in Indonesia was 2,68% higher in cities than in suburban/villages. From women aged 10-54 there are 0.02% pregnant women under 15 years old. This was a descriptive retrospective, study using medical record data of the patients who had premature labour among teenagers acording to age, education, job, marital status, parity, health, head presentation. The results showed that of 31 cases of premature labours in teenagers, 22 cases or 70.96% of them are delivered by women age 18 to 19-year-old, the last education level they had in average is high school which is 64.51%, the majority of them, 93.54% are working as housewives, 83.87% are married, 25 cases or 80.64% of them are primigravida, the highest factors of premature baby, 12.90 % is the ruptured amnion which happened far before the due date of the baby’s delivery, and 90.32% of the case is baby’s head in facing-down position. Conclusion: Premature labours were mostly found in the age group of 18 to 19-year-old with ruptured of amnion long before the baby’s delivery as the highest complication factor, and utmost cases with the baby’s head is in facing-down position.Keywords: preterm labor, teenagers. Abstrak: Menurut WHO ± 13 juta bayi lahir prematur di dunia, dan >1 juta bayi yang lahir prematur meninggal setiap tahunnya. Sekitar 14 juta anak remaja wanita menjadi ibu setiap tahun dan lebih dari 90% dari para ibu muda berada di negara berkembang. Angka kelahiran prematur berkisar 10-20% di Indonesia pada tahun 2009 yang menyebabkan Indonesia masuk dalam peringkat kelima dengan kelahiran prematur terbesar. Berdasarkan Riskesdas 2013 kehamilan umur 10-54 tahun di Indonesia adalah 2,68%, di perkotaan lebih tinggi dibanding perdesaan. Di antara wanita umur 10-54 tahun terdapat kehamilan umur <15 tahun (0,02%). Jenis penelitian ialah deskriptif retrospektif, menggunakan data rekam medik pasien yang melahirkan prematur pada usia remaja berdasarkan umur, pendidikan, pekerjaan, status perkawinan, paritas, penyakit/penyulit, presentasi kepala. Dari 31 kasus persalinan prematur pada remaja, didapatkan paling sering pada usia 18-19 tahun sebanyak 22 kasus (70,96%), pendidikan terakhir terbanyak SMA (64,51%), pekerjaan terbanyak IRT (93,54%), dengan status menikah (83,87%) dan jumlah primigravida 25 kasus (80,64%). Penyakit/penyulit persalinan terbanyak Ketuban Pecah Dini (12,90%) dengan presentasi letak kepala (90,32%). Simpulan: Persalinan prematur pada remaja paling sering ditemukan pada kelompok usia 18-19 tahun dan penyulit tertinggi yaitu ketuban pecah dini dengan jenis presentasi kepala tinggi. Kata kunci: persalinan prematur, kehamilan remaja.